2003
DOI: 10.1108/00346650310499712
|View full text |Cite
|
Sign up to set email alerts
|

Elemental distribution in summer fruits of Pakistan

Abstract: Levels of the selected major and minor elements (Na, K, Ca, Mg, Ni, Cr, Cd, Pb, Zn and Fe) in 11 summer fruits grown in Pakistan were estimated by the flame AAS method based on HNO3/HClO4 wet‐digestion method. The metal concentrations are expressed as X for triplicate sub‐samples with a standard deviation of ±1.0‐1.5 per cent. Of all the minor elements analyzed, Fe was found to be the dominant metal on mean basis as compared with other metals in fruits, its concentration being 14.25mg/kg. The increasing order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 4 publications
3
20
4
Order By: Relevance
“…Contamination by Cd is dependent on the plant species and the growing conditions, with possible aggravations due to irrigation with contaminated water and/or use of fertilizers and herbicides during the cultivation process (Jansson, 2002). Compared with the values found in the present study, Hamurcu et al (2010) determined that the Cd levels of fruit grown near highways are higher compared with the reported values for apples (0.16 µg.g The cadmium content in fruits has been reported to be 0.65-1.34 µg.g -1 (Sattar et al, 1989), 0.09-0.21 µg.g -1 (Zahoor et al, 2003), 0.16-0.24 µg.g -1 (Abou-Arab et al, 1999), 0.002-0.05 µg.g -1 (Radwan & Salama, 2006), 0.1-0.81 µg.g -1 (Duran et al, 2008) and 0.02-0.72 µg.g -1 (Saracoglu et al, 2009). …”
Section: Minerals Analysis By Usn-icp-oescontrasting
confidence: 88%
See 1 more Smart Citation
“…Contamination by Cd is dependent on the plant species and the growing conditions, with possible aggravations due to irrigation with contaminated water and/or use of fertilizers and herbicides during the cultivation process (Jansson, 2002). Compared with the values found in the present study, Hamurcu et al (2010) determined that the Cd levels of fruit grown near highways are higher compared with the reported values for apples (0.16 µg.g The cadmium content in fruits has been reported to be 0.65-1.34 µg.g -1 (Sattar et al, 1989), 0.09-0.21 µg.g -1 (Zahoor et al, 2003), 0.16-0.24 µg.g -1 (Abou-Arab et al, 1999), 0.002-0.05 µg.g -1 (Radwan & Salama, 2006), 0.1-0.81 µg.g -1 (Duran et al, 2008) and 0.02-0.72 µg.g -1 (Saracoglu et al, 2009). …”
Section: Minerals Analysis By Usn-icp-oescontrasting
confidence: 88%
“…According to the World Health Organization (1996), the maximum limit of Pb allowed for food is 10 µg.g -1 . Comparing this limit to the values measured in this study, these fruits are considered acceptable, with lower Pb values than those reported in the literature at 0.48-2.14 µg.g -1 (Altundag & Tuzen, 2011), 1.91 µg.g -1 (Saracoglu et al, 2009), 6.6-9.2 µg.g -1 (Sattar et al, 1989), and 1.66 µg.g -1 (Zahoor et al, 2003). This metal is frequently found in high concentrations in plants grown near highways, as reported by Hamurcu et al (2010) for apples (2.21 µg.g Known for multiple adverse effects on human health, both Pb and Cd are toxic agents associated with environmental contamination and industrial waste.…”
Section: Discussionsupporting
confidence: 69%
“…Many different studies and methods for heavy metal determination in different food stuffs have been reported in the literature including dry, wet and microwave digestion methods to investigate heavy metal levels in cheese, fruits, fruit juices, vegetables, sweets, chocolates, honey, snacks, appetizers, etc. (Soylak et al 2006;Radwan and Salama 2006;Zahoor et al 2003;Yebra and Cancela 2005;Nascentes et al 2004;Saracoglu et al 2004). Sweets including chewing gums and candies are not exactly a food, but it is especially consumed by children and pregnant woman with ingesting or chewing by teeth in mouth.…”
Section: Introductionmentioning
confidence: 99%
“…Fruits principally contain citric, tartaric and malic acids, with pH varying between 2.5 and 4.5. Other constituents of fruits include cellulose and woody fibers, mineral salts, pectin, gums, tannins, coloring matters and volatile oils [4]. However, in the advent of recent heavy metal contamination of the environment, the analysis of TE in seasonal fruit samples has gained considerable importance due to health considerations.…”
Section: Introductionmentioning
confidence: 99%